Kingdom conspiracy : returning to the radical mission of the local church - McKnight, Scot. (Grand Rapid, Michigan : Brazos Press, 2014)
According to Scot McKnight, "kingdom" is the biblical term most misused by Christians today. It has taken on meanings that are completely at odds with what the Bible says. "Kingdom" has become a buzzword for both social justice and redemption so that it has lost its connection with Israel and with the church as a local church. McKnight defines the biblical concept of kingdom, offering a thorough corrective and vision for the contemporary church. The most important articulation of kingdom was that of Jesus, who contended that the kingdom was in some sense present and in some sense in the future. The apostles talked less about the kingdom and more about the church. McKnight explains that kingdom mission is local church mission and that the present-day fetish with influencing society, culture, and politics distracts us from the mission of God: to build the local church. He also shows how kingdom theology helps to reshape the contemporary missional conversation.
Skinny jeans kingdom -- Pleated pants kingdom -- Tell me the kingdom story -- Kingdom mission is all about context -- Kingdom is people -- No kingdom outside the church -- Kingdom mission as church mission -- The king of the kingdom -- Kingdom redemption unleashed -- Kingdom is a moral fellowship -- Kingdom is hope -- Kingdom theses -- Appendix 1: The Constantinian temptation -- Appendix 2: Kingdom today -- After words.
Includes index.
Includes bibliographical references and indexes.
Keywords: Mission of the church; Kingdom of God; Jesus Christ -- Kingdom